DOP28 Venous thromboembolism following discharge from hospital in patients admitted for Inflammatory Bowel Disease. (21st January 2022) - Harvey, P; Coupland, B; Mytton, J; Trudgill, N; De Silva, S
Abstract: Background: Patients admitted to hospital with active Inflammatory bowel disease(IBD) are at increased risk of thromboembolism. Surgical specialties have demonstrated benefits of thromboembolism prophylaxis after hospital discharge in high risk groups. This study aims to identify IBD patients at increased risk and develop a scoring system to recognise them. Methods: Hospital episode statistics data was used to identify all patients admitted for IBD emergently or electively for surgery. All Patients with a thromboembolism within 90 days of hospital discharge were identified. A multilevel logistic regression model was used to identify patient and admission level factors associated with increased risk of thromboembolism. A scoring system to identify higher risk patients was constructed based on this model. Score performance was assessed using bootstrapped data. Results: 201, 779 admissions in 101, 966 patients were included. The rate of thromboembolism within 90 days was 17.24 per 1000 patient years at risk. This was highest in patients admitted as an emergency undergoing surgery (36.91) followed by emergency admission without surgery (15.63) and elective admission for surgery (15.60). The rate of thromboembolism between 180 and 270 days following discharge was 0.84, 1.59 and 1.70 per 1000 patient years at risk respectively. Regression analysis demonstrated that female gender (OR 0.65(95%CI 0.53–0.80), p<0.001), increasing age (49–60 years, (4.73(3.40–6.58), p<0.001), increasing length of stay; 5–7 days (1.77(1.27–2.46), p=0.001), 7–10 days (1.91(1.40–2.60), p<0.001), >10 days (4.04(2.98–5.46), p<0.001), increasing number of prior admissions for IBD in preceding 3 months; 1 (1.36(1.11–1.68), p=0.004), 2 (1.66(1.23–2.22), p=0.001), >2 (2.32(1.67–3.21), p<0.001), Ulcerative Colitis (1.46(1.19–1.79), p<0.001) and admission type compared to Elective surgery (Emergency admission including surgery (1.64(1.15–2.33), p=0.006)), (Emergency admission not including surgery(1.57(1.07–2.32), p=0.023)) were statistically significant associations. In the scoring system, a score >=9 gave a positive predictive value of 1%. The AUC was 0.71(95%CI 0.69–0.72) Conclusion: Patients admitted to hospital have ongoing increased risk of thromboembolism in the 90 day period following discharge. Risk was increased in patients with prolonged length of stay, increasing age, male gender or admitted as an emergency requiring surgery. Higher risk patients were identifiable by a scoring system.